0492 Assessment of exposure to sub-concussive head impacts in former professional soccer players. (21st August 2017) - Cherrie, John; Basinas, Ioannis; Tongeren, Martie van; McElvenny, Damien; Gallo, Valentina; Pearce, Neil
Abstract : There is a lack of information on the most appropriate way to assess exposure to sub-concussive head impacts from heading footballs In terms of relevance for future potential cognitive effects amongst former professional footballers. Reliable quantification of exposure is key to undertaking informative epidemiological studies of cognitive function or neurodegenerative effects amongst former players and is a prerequisite for the design of appropriate interventions to prevent risk of disease. We propose to identify the potential determinants of exposure of chronic sub-concussive head impacts due to heading a football, and how these might relate to the putative disease processes of interest. Information about frequency and intensity of impacts will be collected retrospectively using interviews with subjects, consultation with a panel of former players, analysis of available records, and archive video of games. Important changes that may have affected exposure over time, such as the weight of balls and the pattern of play, will be identified. We will integrate these data into one or more metrics for energy transfer and/or acceleration from head impacts, based on a biomechanical model of the impact process.